Dolphin tale 2 : the junior novel - Reyes, Gabrielle (New York, NY : Scholastic, Inc., 2014)
A baby dolphin found off the coast of Florida is brought to the Clearwater Marine Aquarium for help. There Sawyer and Hazel name her Hope and work to help her.
Based on the motion picture "Dolphin Tale 2."
"Based upon the screenplay written by Charles Martin Smith"--T.p.
4.5
3-6
Keywords: Dolphins -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Dolphins -- Fiction; Human-animal relationships -- Fiction; Dolphins -- Fiction; Human-animal relationship -- Fiction; Movie novels; Movie novels